Pengaruh Work Life Balance dan Stres Kerja Terhadap Turnover Intention PT. Multi Alfa Mandiri Kota Tangerang - Putri, Dian Triana; Nurhadi; Hadi, Seno Sudarmono (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to examine the simultaneous influence of Work-Life Balance and Job Stress on Employee Turnover Intention at PT. Multi Alfa Mandiri, Tangerang City. The population consists of employees at PT. Multi Alfa Mandiri, Tangerang City, with a sample size of 50 respondents using saturated sampling technique. This research employs a quantitative approach, collecting data through questionnaires supported by secondary data. Data analysis was conducted using multiple linear regression. The results indicate that partially, Work-Life Balance (X1) has a significant effect on Turnover Intention with a t-value of 4.640 > t-table 2.012 and sig. 0.000 < 0.05. Job Stress (X2) also has a significant effect with a t-value of 4.161 > t-table 2.012 and sig. 0.000 < 0.05. Simultaneously, Work-Life Balance and Job Stress significantly influence Turnover Intention with an F-value of 117.181 > F-table 3.20. The R Square value of 83.3% shows that both variables collectively affect Turnover Intention, while the remaining 16.7% is influenced by other factors not examined in this study